2021
DOI: 10.3389/fnins.2021.678590
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Satiety Quiescence by Neuropeptide Signaling in Caenorhabditis elegans

Abstract: Sleep and metabolism are interconnected homeostatic states; the sleep cycle can be entrained by the feeding cycle, and perturbation of the sleep often results in dysregulation in metabolism. However, the neuro-molecular mechanism by which metabolism regulates sleep is not fully understood. We investigated how metabolism and feeding regulate sleep using satiety quiescence behavior as a readout in Caenorhabditis elegans, which shares certain key aspects of postprandial sleep in mammals. From an RNA interference-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…A second possibility is for all these neuropeptides to contribute to the execution of dauer behaviors and physiological functions, which is partially supported by our findings that flp-7 and flp-11 are involved in mediating nictation, a dauer-specific behavior. It is not known whether these neuropeptides are also more abundant when regulating their other known roles ( 68 , 81 , 82 , 83 , 84 ) or even whether there would be a general correlation between neuropeptide abundance and usage. It remains curious that almost all quantified neuropeptides are so plentiful, as it seems unlikely that dauers need all of them simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility is for all these neuropeptides to contribute to the execution of dauer behaviors and physiological functions, which is partially supported by our findings that flp-7 and flp-11 are involved in mediating nictation, a dauer-specific behavior. It is not known whether these neuropeptides are also more abundant when regulating their other known roles ( 68 , 81 , 82 , 83 , 84 ) or even whether there would be a general correlation between neuropeptide abundance and usage. It remains curious that almost all quantified neuropeptides are so plentiful, as it seems unlikely that dauers need all of them simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…In many species, sleep deprivation results in increased food intake, while prolonged periods of food deprivation lead to a reduction in metabolic rate and suppression of sleep (Keene et al 2010;Arble et al 2015;Stahl et al 2017;Regalado et al 2017;Goldstein et al 2018). Conversely, animals ranging from the nematode, C. elegans, to humans, increase sleep immediately following a meal, revealing an acute effect of dietary nutrients on sleep regulation (Stahl et al 1983;Murphy et al 2016;Makino et al 2021). Defining how evolution has shaped interactions between sleep, metabolic regulation, and feeding is critical to determine the functions of these traits.…”
Section: Introductionmentioning
confidence: 99%
“…C. elegans has a small and invariant nervous system and sleep is controlled by relatively few neurons. RIS is a GABAergic and peptidergic interneuron that activates during sleep, and its ablation virtually abolishes sleep behavior during molting of developing larvae, in arrested larvae, and in adults following cellular stress [10][11][12][13][14][15][16][17][18][19][20][21]. Optogenetic manipulations showed that acute activation of RIS inhibits wakefulness activity such as feeding and locomotion [10,15], whereas inactivation of RIS inhibits sleep [12,18,22,23].…”
Section: Introductionmentioning
confidence: 99%